Incidence of Knee Pain Beyond 1 Year: Suprapatellar Versus Infrapatellar Approach for Intramedullary Nailing of the Tibia. Issue 9 (September 2019) - Isaac, Marckenley; O'Toole, Robert V.; Udogwu, Ugo; Connelly, Daniel; Baker, Mitchell; Lebrun, Christopher T.; Manson, Theodore T.; Zomar, Mauri; O'Hara, Nathan N.; Slobogean, Gerard P.
Abstract : Objective: To compare the magnitude of knee pain between the suprapatellar (SP) and infrapatellar (IP) approach for tibial nailing in patients who are more than 1 year after injury. Design: Retrospective cohort study. Setting: Academic Level I trauma center. Patients/Participants: All tibia fracture patients 18-80 years of age treated with an intramedullary tibial nail during a 5-year period were retrospectively reviewed for inclusion. The surgical approach was determined by surgeon preference, with 3 of the 9 surgeons routinely using the SP approach. The primary outcome was knee pain during kneeling, with secondary assessments comparing knee pain during resting, walking, and the past 24 hours. Intervention: Intramedullary nailing of a tibia fracture with either the SP or IP approach. Main Outcome Measurements: Knee pain assessed with the Numeric Rating Scale between 0 and 10. A difference of >1.0 was considered to be clinically meaningful. Results: The study group consisted of 262 patients (SP, n = 91; IP, n = 171) with a mean age of 41.4 years (SD = 16.6). The median follow-up was 3.8 years (range: 1.5–7.0). No difference in knee pain during kneeling was detected between the surgical approaches (IP: 3.9, SP 3.8; P = 0.90; mean difference: −0.06, 95% confidence interval, −1 to 0.9). Similarly, no differences were detected in average knee pain scores at rest (IP: 2.0, SP: 2.0; P = 1.00), walking (IP: 2.7, SP 3.0; P = 0.51), or the last 24 hours (IP: 2.6, SP 2.9; P = 0.45). Conclusions: In contrast to a study conducted by Sun et al, in which there was a statistical difference in knee pain between the SP and IP surgical approaches, we did not detect any statistical or clinical differences in knee pain between the SP and IP surgical approaches among patients with greater than 12 months of follow-up. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.